Can a Brief Relaxation Exercise Modulate Placebo or Nocebo Effects in a Visceral Pain Model? - Elsenbruch, Sigrid; Roderigo, Till; Enck, Paul; Benson, Sven (Frontiers in Psychiatry, 2019)
Translational research aiming to elucidate mediators and moderators of placebo and nocebo effects is highly relevant. This experimental study tested effects of a brief progressive muscle relaxation (PMR) exercise, designed to alter psychobiological stress parameters, on the magnitude of placebo and nocebo effects in a standardized psychosocial treatment context. In 120 healthy volunteers (60 men, 60 women), pain expectation, pain intensity and pain unpleasantness in response to individually-calibrated rectal distensions were measured with visual analogue scales during a baseline. Participants were then randomized to exercise PMR (relaxation group: N=60) or a simple task (control group: N=60), prior to receiving positive (placebo), negative (nocebo) or neutral suggestions regarding an intravenous administration that was in reality saline in all groups. Identical distensions were repeated (test). State anxiety, salivary cortisol, heart rate and blood pressure were assessed repeatedly. Data were analyzed using analysis of covariance, planned Bonferroni-corrected group comparisons, as well as exploratory correlational and mediation analyses. Treatment suggestions induced group-specific changes in pain expectation, with significantly reduced expectation in placebo and increased expectation in nocebo groups. PMR had no discernable effect on pain expectation, state anxiety or cortisol, but led to significantly lower heart rate and systolic blood pressure. Relaxation significantly interacted with positive treatment suggestions, which only induced placebo analgesia in relaxed participants. No effects of negative suggestions were found in planned group comparisons, irrespective of relaxation. Exploratory correlation and mediation analyses revealed that pain expectation was a mediator to explain the association between treatment suggestions and pain-related outcomes. Clearly, visceral pain modulation is complex and involves many cognitive, emotional, and possibly neurobiological factors that remain to be fully understood. Our findings suggest that a brief relaxation exercise may facilitate the induction of placebo analgesia by positive when compared to neutral treatment suggestions. They underscore the contribution of relaxation and stress as psychobiological states within the psychosocial treatment context – factors which clearly deserve more attention in translational studies aiming to maximize positive expectancy effects in clinical settings.